Holidays, festivals, and celebrations of the world dictionary : detailing nearly 2,500 observances from all 50 states and more than 100 nations : a compendious reference guide to popular, ethnic, religious, national, and ancient holidays ... - Henderson, Helene, 1963- (Detroit, MI : Omnigraphics, 2005)
"Contains information about nearly 2,500 holidays, festivals, holy days, feasts and fasts, and other observances, including popular, secular, and religious celebrations for more than 100 countries and every state of the United States"--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Holidays -- Dictionaries; Festivals -- Dictionaries